2017
DOI: 10.1128/jcm.02092-16
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Microbiological Aspects of β-Lactam Resistance in Staphylococcus lugdunensis

Abstract: Antimicrobial susceptibility results from broth microdilution MIC testing of 993 Staphylococcus lugdunensis isolates recovered from patients at a tertiary care medical center from 2008 to 2015 were reviewed. Ninety-two oxacillin-susceptible isolates were selected to assess the accuracy of penicillin MIC testing, the penicillin disk diffusion test, and three ␤-lactamase tests, including the cefoxitin-induced nitrocefin test, penicillin cloverleaf assay, and penicillin disk zone edge test. The results of all phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
(21 reference statements)
2
11
0
1
Order By: Relevance
“…Fosfomycin resistance-associated gene was highly conserved among the 21 strains while the distribution of penicillin and fusidic acid resistance genes was variable between isolates. This finding is in accordance with the results of McHardy et al (2017). who showed that the blaZ gene was detected in 39.1% of oxacillin-susceptible S. lugdunensis isolates.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Fosfomycin resistance-associated gene was highly conserved among the 21 strains while the distribution of penicillin and fusidic acid resistance genes was variable between isolates. This finding is in accordance with the results of McHardy et al (2017). who showed that the blaZ gene was detected in 39.1% of oxacillin-susceptible S. lugdunensis isolates.…”
Section: Discussionsupporting
confidence: 93%
“…S. lugdunensis exhibits a highly conserved antibiotic susceptibility to most anti-staphylococcal antibiotics, which may be related to these different barriers against the integration of foreign DNA (Higaki et al, 1999; McHardy et al, 2017). Indeed, only one plasmid carrying an antibiotic resistance gene ( tetK ) was identified in a newly sequenced genome.…”
Section: Discussionmentioning
confidence: 99%
“…The need for individualized AST methods and breakpoints for CoNS species was first shown with S. lugdunensis. S. lugdunensis isolates positive for mecA were found to have oxacillin MICs of Ն4 g/ml consistent with the higher breakpoint set for S. aureus (8)(9)(10). This is not surprising, given that S. lugdunensis, while classified as CoNS, behaves clinically in a manner similar to that seen with S. aureus (2).…”
mentioning
confidence: 54%
“…17 Of note, Staphylococcus lugdunensis should be treated in a similar manner to S. aureus. 167 For enterococcal CR-BSI, ampicillin is the first choice for ampicillin-susceptible strains, vancomycin for those which are ampicillin resistant, and daptomycin or linezolid for vancomycin-resistant (VRE) strains. 168 The role of combination therapy for treating enterococcal CR-BSI without endocarditis is unresolved, especially for VRE.…”
Section: Targeted Antimicrobial Treatment According To the Specific Pmentioning
confidence: 99%